FACTORS INFLUENCING THE DECLINE IN MARRIAGE RATES IN PADANGSIDIMPUAN - Muthiatul Khairiyah Ritonga; Rony Hamdani Sirega; Yusrina Gultom; Husnatul Hamidiyah (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This study discusses the factors that influence the decline in the marriage rate in Padangsidimpuan, nowadays many people including the government, historians, and the general public, are paying attention to the decline in the marriage rate. This downward trend is increasingly visible in several areas in Indonesia, such as Padangsidimpuan. Many factors influence the decline in the number of marriages. Humans are by nature social creatures, who cannot live alone without the help of others. Therefore, humans are created in pairs to be able to share emotional and physical. Marriage as a basic social institution not only reflects the relationship between two individuals, but also has a significant impact on social structure, family sustainability, and the welfare of society as a whole. The decline in the number of marriages can cause various problems and the economy. There are certain factors that contribute to this change, such as shifts in values ​​or economic factors. Knowing the views on this is important to formulate appropriate policies and find effective solutions. In this article, the research method used is the writing method using library research by collecting various sources of library studies.